Scaffolding in guided inquiry learning with google classroom: Effect on physics conceptual understanding - Adis Veliana Anjani; Murih Rahayu; Ardian Asyhari (Jurnal Inovasi Pendidikan IPA, 2022)
The purpose of this study is to examine the impact of student's conceptual understanding on the topic of elasticity and Hooke's Law utilizing a scaffolding-based technique guided inquiry facilitated by Google Classroom. The quasi-experimental design method is used in this investigation. This study's design includes all class XI students from one of Bandar Lampung's schools for the 2018/2019 academic year. This study employed systematic random sampling to obtain 30 students in each of the experimental and control groups. The research instrument employed was a concept understanding exam consisting of 20 two-tier diagnostic questions with a reliability level of 0.84 in the high category and suitability. The results of this study show an average value of 58.6 in the control group and 73 in the experimental group. The hypothesis results reveal that the significant value of the t-count t-table with the choice H0 is rejected, and the effect size test results suggest that d = 1.08 where d 0.8. These findings imply that the experimental class outperforms the control class. As a result, the scaffolding-based guided inquiry technique supported by Google Classroom has the potential to alter students' physics conceptual understanding.